Ensino e aprendizagem de evolução biológica: uma análise da evolução conceitual em sala de aula - Macena, Marcílio Gomes (2020)
In this research, we seek to investigate how the practices carried out regarding teaching strategies concerned with promoting conceptual changes, underpin and influence the development of the teaching and learning process of Biological Evolution. Thus, we used the analysis of conceptual evolution in the classroom, within the context of basic education based on teaching strategies aimed at conceptual change. Before the intervention process, we carried out a survey of previous conceptions from the construction and application of a questionnaire that had three open questions for the identification of different conceptions about Biological Evolution, differentiating the scientific conception from the non-scientific conceptions present in life everyday life, which made it possible to identify possible conceptual inaccuracies. After the survey, there was an intervention process subsidized by research teaching through an Investigative Teaching Sequence (SEI) as a didactic proposal to provide Conceptual Evolution. The intervention was divided into seven classes that sought to articulate the explanation of the concepts, the promotion of cognitive conflict for the restructuring of the concepts, and the construction of knowledge from the proposal of teaching by investigation. These classes were structured based on the procedure of proposing problem questions, raising hypotheses and systematizing knowledge through readings, discussions and guided debates. We used to carry out these classes: projection of thematic images and cartoons; internet searches; dynamics for survey and discussion of concepts; practice for hypothesis testing; besides texts for systematization. From the analysis of the results, it was possible to perceive the conceptual evolution through the accommodation of the scientific explanatory model in the conceptual network of students, with the conceptual exchange. Thus, in the three questions in the questionnaires, the presence of accommodation predominated. In the first question, regarding the concept of Biological Evolution, 45% of the students accommodated the scientific explanation. In the second question, alluding to the concept of adaptation, 55% of students accommodated the scientific explanatory model. However, it was in the third question, which deals with the concept of Natural Selection, that the greatest accommodation of the scientific explanation was noted, observed in 65% of those surveyed. Still, it was observed the partial assimilation of the scientific explanation, present in the answers of 25% of the students who answered the first question about the concept of Biological Evolution. These students, who during the intervention process, reproduced the scientific discourse, but, in the answers of the post-test questionnaire, they made explicit part of the non-scientific discourse present in their previous conceptions. Therefore, we conclude that the option for an Investigative Teaching Sequence, can constitute an appropriate instructional strategy for the construction of knowledge and the promotion of conceptual evolution. Thus, confirming what the results obtained during the teaching and learning process indicate, the methodology used here showed that most of the results reaffirm the presence of conceptual evolution, from the partial assimilation of the scientific explanatory model or the presence of accommodation of scientific explanation in the students' conceptual network.